Paytm : the Lucky Lifafa campaign - Titus, Nidhi, (SAGE Business. Cases., 2019)
The Indian digital payment market was estimated to grow to around USD 700 billion - USD 1 trillion by 2022. This has seen a number of players entering the market to challenge Paytm which aimed to maintain its prominent position in the Indian mobile wallet space. To increase its user base and use-cases, Paytm introduced the Lucky Lifafa campaign to provide Indian users a novel way of gifting money. The campaign was similar to the Red Envelope campaign used by WeChat to garner a wide user base in China. In spite of gift-giving being an integral part of Indian culture, the acceptance of Lucky Lifafa among Indian users was significantly different from that of the Red Envelope among Chinese users. This case describes the Lucky Lifafa campaign and the context in which it was executed, thus highlighting the differences in the process of gifting between Chinese and Indian societies. Additionally, the case also provides details of existing and upcoming players in the mobile wallet market space in India.